Senescent cell population with ZEB1 transcription factor as its main regulator promotes osteoarthritis in cartilage and meniscus. Issue 3 (23rd December 2022) - Swahn, Hannah; Li, Kun; Duffy, Tomas; Olmer, Merissa; D'Lima, Darryl D; Mondala, Tony S; Natarajan, Padmaja; Head, Steven R; Lotz, Martin K
Abstract : Objectives: Single-cell level analysis of articular cartilage and meniscus tissues from human healthy and osteoarthritis (OA) knees. Methods: Single-cell RNA sequencing (scRNA-seq) analyses were performed on articular cartilage and meniscus tissues from healthy (n=6, n=7) and OA (n=6, n=6) knees. Expression of genes of interest was validated using immunohistochemistry and RNA-seq and function was analysed by gene overexpression and depletion. Results: scRNA-seq analyses of human knee articular cartilage (70 972 cells) and meniscus (78 017 cells) identified a pathogenic subset that is shared between both tissues. This cell population is expanded in OA and has strong OA and senescence gene signatures. Further, this subset has critical roles in extracellular matrix (ECM) and tenascin signalling and is the dominant sender of signals to all other cartilage and meniscus clusters and a receiver of TGFβ signalling. Fibroblast activating protein (FAP) is also a dysregulated gene in this cluster and promotes ECM degradation. Regulons that are controlled by transcription factor ZEB1 are shared between the pathogenic subset in articular cartilage and meniscus. In meniscus and cartilage cells, FAP and ZEB1 promote expression of genes that contribute to OA pathogenesis, including senescence. Conclusions: These single-cell studies identified a senescent pathogenic cell cluster that is present in cartilage and meniscus and has FAP and ZEB1 as main regulators which are novel and promising therapeutic targets for OA-associated pathways in both tissues.